2022
DOI: 10.3390/molecules27041230
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Transport Mechanism of Puerarin and Gastrodin and Their Interaction on the Absorption in a Caco-2 Cell Monolayer Model

Abstract: Puerarin (PUR) and gastrodin (GAS) are often used in combined way for treating diseases caused by microcirculation disorders. The current study aimed to investigate the absorption and transportation mechanism of PUR and GAS and their interaction via Caco-2 monolayer cell model. In this work, the concentration in Caco-2 cell of PUR and GAS was determined by HPLC method. The bidirectional transport of PUR and GAS and the inhibition of drug efflux including verapamil and cyclosporine on the transport of these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Gastrodin (Figure 1A) is an active component of Gastrodia elata Blume, chemically known as 4-hydroxybenzyl alcohol-4-O-β-d-glucopyranosid [14]. The treatment of human normal hepatocytes cells (LO2), human renal proximal tubular cells (HK2), and normal human astrocytes (NHA) with different concentrations (0, 2.5, 5, 10, 20, 40, and 80 µM) of gastrodin revealed that 2.5, 5, 10, and 20 µM concentrations of gastrodin were not cytotoxic to LO2, HK2, and NHA after both 24 and 48 h (Figure 1B).…”
Section: Gastrodine Exhibited Prominent Anti-tumor Effects In Vitromentioning
confidence: 99%
“…Gastrodin (Figure 1A) is an active component of Gastrodia elata Blume, chemically known as 4-hydroxybenzyl alcohol-4-O-β-d-glucopyranosid [14]. The treatment of human normal hepatocytes cells (LO2), human renal proximal tubular cells (HK2), and normal human astrocytes (NHA) with different concentrations (0, 2.5, 5, 10, 20, 40, and 80 µM) of gastrodin revealed that 2.5, 5, 10, and 20 µM concentrations of gastrodin were not cytotoxic to LO2, HK2, and NHA after both 24 and 48 h (Figure 1B).…”
Section: Gastrodine Exhibited Prominent Anti-tumor Effects In Vitromentioning
confidence: 99%